The Bioeconomy Model in Future Sustainable Development - Ipate, Nicolae; David, Katalin Gabriela; Ipate, Ipate; Bogdan, Alexandru (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
The future of sustainable development is the bioeconomy with the ―global‖ solution; both global and local action for developed the renewable energy generation. When local solutions are implemented is being laid for global solutions are positive affect the national economy. The implementation of the bioeconomy strategy used by society to prevent urgent problems, such as increasing competition for natural resources, climate change, rural sustainable development. The bioeconomy is a new economic and social order and promotes systemic change from using non-renewable resources to renewables. Bioeconomy reveals that production, which involves the transformation of a limited stock of matter and energy, but respecting the same laws that govern entropy closed systems, the entropy or unavailable matter and energy in the forms tend to increase continuously. Economic growth not only increases the apparent output per unit of inputs, which is performed using finite stock of matter and energy in the world. The current economy is based on fossil fuels and other material inputs suffering entropic degradation, both in the raw material extraction and pollution. The production, even if technical progress leads to lower overall yields. The idea of a steady state as the final economic growth that perpetuated indefinitely pendulum model is an impossibility.